2017
DOI: 10.1074/jbc.m116.770735
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Alterations Contribute to Enhanced Inflammatory Cytokine Production in Irgm1-deficient Macrophages

Abstract: Edited by Luke O'NeillThe immunity-related GTPases (IRGs) are a family of proteins that are induced by interferon (IFN)-␥ and play pivotal roles in immune and inflammatory responses. IRGs ostensibly function as dynamin-like proteins that bind to intracellular membranes and promote remodeling and trafficking of those membranes. Prior studies have shown that loss of Irgm1 in mice leads to increased lethality to bacterial infections as well as enhanced inflammation to non-infectious stimuli; however, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 95 publications
(135 reference statements)
3
23
0
Order By: Relevance
“…In liver, the top KDs for B6 DEGs were mostly related to sterol biosynthesis such as Dhcr7, Fdft1, and Lss. The top KDs for DBA included Fgf21, a target of ChREBP and a metabolic regulator for insulin sensitivity and obesity (6; 35), Insig2, a negative regulator of SREBP targeting lipid metabolism (36), Irgm, which induces inflammatory cytokine production (37), and Arntl, a key circadian rhythm gene. FVB top liver KDs included Itih3, implicated in liver glutathione metabolism (38), and Akr1d1, important for bile acid and steroid hormone metabolism (39).…”
Section: Wkda Analysis Prioritized Strain-and Tissue-specific Key Drimentioning
confidence: 99%
“…In liver, the top KDs for B6 DEGs were mostly related to sterol biosynthesis such as Dhcr7, Fdft1, and Lss. The top KDs for DBA included Fgf21, a target of ChREBP and a metabolic regulator for insulin sensitivity and obesity (6; 35), Insig2, a negative regulator of SREBP targeting lipid metabolism (36), Irgm, which induces inflammatory cytokine production (37), and Arntl, a key circadian rhythm gene. FVB top liver KDs included Itih3, implicated in liver glutathione metabolism (38), and Akr1d1, important for bile acid and steroid hormone metabolism (39).…”
Section: Wkda Analysis Prioritized Strain-and Tissue-specific Key Drimentioning
confidence: 99%
“…For instance, Irgm1 -deficient mice suffer from hyperinflammation (Maric-Biresev et al, 2016, Schmidt et al, 2017). In human cells, IRGM appears to play a central role in xenophagy, which we envision clears pathogens without attendant inflammasome activation (Chauhan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our cell culture observations, we found that deletion of Irgm1 and Irgm3 partially reversed the caspase-4-driven hyperinflammatory response of Irgm2-deficient animals, as evident by the intermediate IL-1β serum levels of endotoxemic panIrgm-/-relative to WT and Irgm2-/-mice ( Fig 7C). TNF serum levels were comparable across the different genotypes tested ( Fig 7C), indicating that deletion of all Irgm isoforms not only partially normalized the sensitized caspase-4 pathway of Irgm2-/-mice but also tempered the excessive TLR4 signaling pathway of Irgm1-/-mice (Bafica et al, 2007, Schmidt et al, 2017. Lastly, we found that the deletion of all Irgm genes increased survival of endotoxemic mice to WT or near WT levels (Figs 7D and EV5B), supporting a model, according to which dysregulated Irgm isoform expression rather than merely Irgm2 loss-of-function drives the pathological inflammation in endotoxemic Irgm2-/-mice.…”
Section: Immune Homeostasis Is Partially Restored In Mice Deficient Fmentioning
confidence: 87%
“…The exact functional relationship between hIRGM isoforms and their mouse Irgm orthologs is currently not well defined. However, several recent studies demonstrated that hIRGM and mouse Irgm1 commonly regulate cellular processes that include mitochondrial dynamics (Henry, Schmidt et al, 2014, Liu, Gulati et al, 2013, Schmidt, Fee et al, 2017, Singh, Ornatowski et al, 2010, autophagic flux (Gutierrez, Master et al, 2004, Singh, Davis et al, 2006, Traver, Henry et al, 2011 and NLRP3 inflammasome activation (Mehto, Jena et al, 2019). The parallels between human and mouse IRGMs extend beyond these cell culture phenotypes: similar to hIRGM, Irgm1 attenuates intestinal inflammation (Liu et al, 2013, Rogala, Schoenborn et al, 2018 and promotes host survival during LPS-induced sepsis (Bafica, Feng et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation